2019
DOI: 10.1186/s12870-019-1683-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses of reactive oxygen species and methylglyoxal metabolisms to magnesium-deficiency differ greatly among the roots, upper and lower leaves of Citrus sinensis

Abstract: Background Magnesium (Mg)-deficiency is one of the most prevalent physiological disorders causing a reduction in Citrus yield and quality. ‘Xuegan’ ( Citrus sinensis ) seedlings were irrigated for 16 weeks with nutrient solution containing 2 mM (Mg-sufficiency) or 0 mM (Mg-deficiency) Mg(NO 3 ) 2 . Thereafter, we investigated the Mg-deficient effects on gas exchange and chlorophyll a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 81 publications
(141 reference statements)
1
27
0
Order By: Relevance
“…ATP sulfurylase (ATPS), Cys synthase (CS), adenosine 5′-phosphosulphate (APS) reductase (APR), sulfite reductase (SiR), γ-glutamylcysteine synthetase (γGCS), Gly I and Gly II were extracted according to Cai et al [23]. ATPS, CS, Sir and APR activities were assayed according to Guo et al [29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP sulfurylase (ATPS), Cys synthase (CS), adenosine 5′-phosphosulphate (APS) reductase (APR), sulfite reductase (SiR), γ-glutamylcysteine synthetase (γGCS), Gly I and Gly II were extracted according to Cai et al [23]. ATPS, CS, Sir and APR activities were assayed according to Guo et al [29].…”
Section: Methodsmentioning
confidence: 99%
“…ATPS, CS, Sir and APR activities were assayed according to Guo et al [29]. γGCS was assayed as described previously [23]. Gly I and Gly II were assayed according to Guo et al [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in surplus light energy, which provides reducing equivalents with molecular oxygen to form ROS. Meanwhile, recent studies suggest that sugar accumulation is not the only cause of ROS generation, as the oxidative damage is detected in leaves of Mgdeficient rice before sugars accumulate (Kobayashi et al, 2013b(Kobayashi et al, , 2018 and roots of Mg-deficient sweet orange (Cai et al, 2019). Apart from that, a decrease in leaf transpiration is reported in Mg-deficient rice (Kobayashi et al, 2013b) and maize (Jezek et al, 2015), and this is suggested to be responsible for chlorosis development (Kobayashi et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its vital roles in the normal growth and development of higher plants, less attention has been paid to Mg in comparison to nitrogen (N), phosphorus (P), and potassium (K) [6]. Mg-deficiency, one of the most common physiological disorder influencing productivity and quality of crops including Citrus , is being intensified in intensive agricultural systems, where N, P, and K fertilizers have been heavily applied [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%